Ultrasound guided versus land mark technique for internal jugular central venous catheterization in cardiac surgical patients- a randomized trial - Parajuli, Santosh Sharma; Pokharel, Jeju Nath (Journal of Society of Anesthesiologists of Nepal, 2016)
Background: Catheterization of internal jugular vein can be achieved by either anatomical landmark technique or the ultrasound guided technique. The objective of our study is to find out if ultrasound guided technique could be beneficial in placing central venous catheters by improving the success rate by reducing the number of attempts, decreasing the access time and decreasing the complications rate in comparison to the landmark technique. Methods: Fifty patients scheduled for cardiac surgery requiring central venous cannulation of the right internal jugular vein were divided into two groups: ultrasound guided group ‘U’ and the landmark group ‘L’, each consisting of 25 patients with age more than 15 years. The outcomes were compared in terms of success rate, time taken for successful cannulation and rate of complications. Results: The two groups were comparable in terms of age, weight, heart rate and blood pressure. The mean number of attempts for successful cannulation was 1.08±0.277 and 1.40±0.764 (p=0.055), the time taken in seconds for successful cannulation was 108.56±27.822 and 132.08±72.529 (p=0.137) and the overall complication rate was 0% (0 out of 25) and 32% (8 out of 25) (p=0.02) in the ultrasound guided and the landmark technique group respectively. Conclusion: Ultrasound guided central venous catheterization of internal jugular vein is comparable to the landmark technique in terms of number of attempts and the time required for successful cannulation. Ultrasound guided technique is much safer than the landmark technique to reduce the overall complications rate during central venous cannulation.